KIAT GURU PENDIDIKAN JASMANI DALAM MENDIRIKAN BISNIS OLAHRAGA - Amat Komari (Jurnal Pendidikan Jasmani Indonesia, 2008)
Among the spreading of shopping centers bring amenity for amount of people; not aside from Physical Education teacher who interested for a business. Someones shopping activity in fulfilling daily need, reading news, listening radio, television, transport service and also private vehicle for transportation fluency; all those represent activity of business for the existence of service provider and consumer side. Some needs of that human being represented business field to others so that the interaction of various needs will create business fields, not aside from sport business, for example founding sport shop, training, organizing a game, or sport activities and also serve the needs of athletes such as clothes, food and also calorie-contained beverage. Sport businesses in Indonesia are in partial existed, but such condition still needs the stakeholder touch in order to obtain more maximal result. In National Seminar of Sportsmanship Industry, it have been told some business chances to public that sport-related company, included home industry (e.g. shuttlecock, sport t-shirt, medal graver, self-defense uniform, glove softball, event organizer, etc.) which have expanded themselves so that necessary to snuggle up to be Sport Industry. The Law of National Sportsmanship System has given chances for every citizen to plunge in sport business world, not aside from Physical Education teacher. Consider their involvements, Physical Education teacher with their activity quite a lot related to sport; of course they understand so much the needs of sport perpetrators which represent potential business field for. In starting or developing sport business, Physical Education teacher needs certain tricks, such as: (1) have strong willingness to try by stocked of never give up spirit as well as learning desire, (2) the run-business is easy reached in ability, management, and monetary source, and also that activity have to pleasant, (3) seeing market potency and society needs and also majoring customer satisfaction, (4) in attracting the customer purchasing ability, its necessary using cost leadership strategy, and (5) for managed-company survival, its using forwards, rear, and horizontal integration strategies. Keywords: Business, Sport, Physical Education.